2016
DOI: 10.1111/ijn.12482
|View full text |Cite
|
Sign up to set email alerts
|

Nursing care in multifunctional small group homes providing day, visiting and overnight services for older people living at home

Abstract: Katahira N, Tsukasaki K. International Journal of Nursing Practice 2016; 22: 605-615 Nursing care in multifunctional small group homes providing day, visiting and overnight services for older people living at homeHome care programs for older people have been developed around the world. Nurses are key to these programs. The aim of this study is to explore details of the nursing activities used in group homes to provide a basis for describing effective nursing practices in such facilities. A self-administered qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…End-of-life care is also discussed in 17 practice reports of nurses involved in shokibo in Japan 18 which state that users need to be watched over until end-of-life care. A higher proportion of people die at medical institutions in Japan than they do in other countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…End-of-life care is also discussed in 17 practice reports of nurses involved in shokibo in Japan 18 which state that users need to be watched over until end-of-life care. A higher proportion of people die at medical institutions in Japan than they do in other countries.…”
Section: Discussionmentioning
confidence: 99%
“…Research in eight European countries has also found that interruptions to daytime schedules are strongly associated with the family carer’s burden of nursing care. 17 This is the practice of making arrangements for flexible care service, and, as pointed out by Katahira and Tsukasaki, 18 making arrangements to become a part of a user’s and the user’s family’s lives at home is a major feature of this practice.…”
Section: Discussionmentioning
confidence: 99%
“…There are several limitations to this study. First, the response rate was low, as with previous studies [ 35 ], and the responses may have come from facilities that are positively involved in end-of-life care. Second, we asked the care planners to respond to the quality of end-of-life care by recalling a patient who had died in the facility, which is not the same as the quality of end-of-life care as judged by the PWD or their family.…”
Section: Discussionmentioning
confidence: 90%
“…Continuing medical education for nurses providing home nursing services to elderly patients is of great importance. In the study of Katahira and Tsukasaki, 12 it was found that nurses are key to home nursing services and that it might be advantageous to increase nursing staffing and provide care guidelines and training opportunities to improve nurses’ self-efficacy. In our study, the nurses providing home nursing services to elderly patients were all from large public general hospitals and so the number of nurses was sufficient.…”
Section: Discussionmentioning
confidence: 99%